2021
DOI: 10.1016/j.crphar.2021.100019
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols-rich naringenin nanoemulgel for the management of diabetic wound: Fabrication, characterization and comparative in vitro evaluations

Abstract: The present research had been attempted to formulate and characterize tocotrienols-rich naringenin nanoemulgel for topical application in chronic wound conditions associated with diabetes. In due course, different phases of the nanoemulsion were chosen based on the solubility study, where combination of Capryol 90 and tocotrienols, Solutol HS15, and Transcutol P were selected as oil, surfactant, and cosurfactant, respectively. The nanoemulsions were formulated using the spontaneous emulsification method. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…is low zeta potential is due to the nonionic surfactant incorporated in our formulation. Incorporation of these globules in the polymeric matrix will hinder the movement of the globules, thereby imparting the stability of the formulation [15]. Further, the negative charge of the dispersed drugloaded oil globules might be due to the presence of anionic groups in the cosurfactant and oil core [14].…”
Section: Characterization Of the Formulation For Globulementioning
confidence: 99%
See 2 more Smart Citations
“…is low zeta potential is due to the nonionic surfactant incorporated in our formulation. Incorporation of these globules in the polymeric matrix will hinder the movement of the globules, thereby imparting the stability of the formulation [15]. Further, the negative charge of the dispersed drugloaded oil globules might be due to the presence of anionic groups in the cosurfactant and oil core [14].…”
Section: Characterization Of the Formulation For Globulementioning
confidence: 99%
“…e polymeric networks in this architecture allow entrapping the dispersed globules promoting the stability of the formulation following incorporation of lipidic agents within the oil core of oil-in-water nanoemulsion. is NEG platform possesses the potential of enhanced solubility of lipophilic drugs, sustained release of the entrapped therapeutic agents, superior topical applicability, biocompatibility, and biodegradability [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been used for drug delivery at different body sites such as buccal, gastrointestinal, nasal, rectal, vaginal, and ocular, as it offers several advantages [9,10]. It is described as the interaction resulting from attractive forces between synthetic or natural polymers with the mucous membrane [11,12]. Figure 1 is an illustrative diagram showing the mechanism of mucoadhesion.…”
Section: Mucoadhesive Polymeric Approachmentioning
confidence: 99%
“…The beneficial effect of tocotrienols in dermatology especially in treating melasma and skin inflammation has also been reported [ 10 – 13 ]. Zampieri et al [ 14 ] and Eileen et al [ 15 ] reported on the positive effects of topical vitamin E in surgical wound repair. Although the effect of tocotrienols in dermatology has been shown, to the best of our knowledge, in vitro and in vivo studies using red palm oil (RPO), which contains high amounts of carotenoids (500-700ppm) and vitamin E (500-1000ppm tocopherols and tocotrienols) in wound healing is limited.…”
Section: Introductionmentioning
confidence: 99%